Executive clemency: comparative and empirical perspectives - Pascoe, Daniel; Novak, Andrew (Routledge research in human rights law, 2021)
"This book builds on existing academic scholarship and expands the limited geographical It relays the latest state of knowledge on the topic and employs case studies, doctrinal legal analysis, historical research, and statements by clemency decision-making authorities, in explaining why clemency varies so considerably across global legal and political systems. In addition, it includes contributions encompassing international law, transitional justice, and innocence and wrongful convictions, as well as on jurisdictions that are historically under-researched"--